Anaerobic Co-Digestion of Water Hyacinth (E. crassipes) with Ruminal Slaughterhouse Waste for Biogas Production - Omondi, Erick Auma; Njuru, Peter Gikuma; Ndiba, Peter Kuria (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
The use of biomass as renewable energy source is of interest in reducing dependence on fossil fuels and associated impacts of climate change. Water hyacinth (WH), an invasive aquatic plant of environmental concern has large biomass that is available for biogas production. Co-digestion of this largely lignocellulose biomass with other substrates may correlate process parameters and improve biogas production. This study evaluated co-digestion of WH biomass with various mix proportions of ruminal slaughterhouse waste (RSW) at 24, 32 and 37°C in order to assess the optimum proportion and temperature. The rate of biomethanation increased with temperature from 0.23 at 24ºC to 0.75 and 0.96 at 32ºC and 37ºC, respectively, and similarly methane yield improved from 14 at 24ºC to 40 and 52 L/kg air dried water hyacinth at 32ºC and 37ºC respectively. A WH: RSW ratio of 30% showed optimum acclimatization and methane yield in a residence time of 60 days. The duration of the initial drop in pH that indicates hydrolysis stage decreased with increase in proportion of RSW, indicating faster hydrolysis and fermentation processes. Longer and stable latter alkaline pH zone suggested improved biomethanation and greater biogas production. Co-digestion with 30% RSW at 24ºC improved biogas yield by 75% from 8.05 to 14.09L/Kg biomass, methane component of biogas by 9% from 59 to 68% and reduced the retention time for substrate by 36%, suggesting synergy in co-digestion with respect to biogas quality. Changing the temperature from 24 to 32ºC increased the yield by 186% and reduced retention time by 73%. The results demonstrated synergy in co-digestion of the two substrates and the process dynamics that are useful in a possible process commercialization. ©2019. CBIORE-IJRED. All rights reserved